Experiences of engineering thermodynamics students during online learning: Lessons for post-pandemic - Daniel Raphael Ejike Ewim; Sogo Mayokun Abolarin; Temi Olatunji Scott; Johnson Ayodele Opateye; Maxwell Emmanuel Uduafemhe; Obafemi Oyelakin Olatunji (The Journal of Engineering and Exact Sciences)
Since the outbreak of the COVID-19 pandemic, the education sector has been seriously impacted, leading to the migration of academic offerings to online learning mode. This investigation focuses on the experiences of engineering students offering Thermodynamics as a subject at a University of Technology in South Africa, as they transition to online academic platforms. Resource availability, such as a quantitative learning platform and access to computer laboratories on campus, as well as other institutional supports, were evaluated. A total of 100 students offering the Engineering Thermodynamics module participated in the surveys and responded to the questionnaire. The study identified various constraints that affected the students' learning experience due to the online learning format, including connectivity issues, time management, inadequate university support, limited understanding of online learning platforms, and high cost of data. Various strategies were recommended to address the challenges faced by engineering students during the transition to online learning. By implementing these strategies, the online learning experience can be enhanced for students facing similar challenges in their academic pursuits.